Non-destructive testing to identify different failures in composite laminates - Toh, Zheng Jie (Nanyang Technological University, 2021)
Conventional non-destructive testing of carbon composite components in aircrafts are highly time consuming, being overly reliant on excessive inspection to detect barely visible internal damages. Processes like the ultrasonic phased array testing requires significant time to complete inspection the components of an aircraft. Furthermore, the nature of the material allows for barely visible impact damages (BVID) to occur. BVID are a form of impact damage that provide minimal surface damage while hiding significant internal damages. These issues however can be resolved through the implementation of structural health monitoring systems. These monitoring systems are active systems, having the potential to constantly detect external forces and impacts via sensors within the structures of components during flight and ground operations. This study aims to distinguish and correlate the signal emissions of piezo ceramic sensors upon experiencing BVID. Energy required to fabricate BVID on carbon composite laminates were first determined through the use of quasi-static indentation and ultrasonic immersion tank testing. Subsequently, pristine and sensor embedded carbon composite laminates were then impacted via a low velocity impact test to induce BVID for further analysis. Development of the relationship between the sensor signal patterns to the degree of damage will be of beneficial use for further research of structural health monitoring in the aviation industry.